Becoming Homebaked - Jones Samantha (Cultural Science)
This paper examines the democratic co-production between the artist Jeanne Van Heeswijk, the Liverpool Biennial, local citizens and its local and global social network of members, as together they develop alternatives to cultural and economic regeneration. In a neighbourhood that has suffered from over a decade of stalled regeneration programmes, Homebaked is located on the high street just a few steps from the famous Liverpool Football Club. It was set up as the first UK urban Community Land Trust (CLT) to design customised housing, support social enterprises, enhance the wellbeing of the community and open a co-operative community-run bakery. Homebaked’s principle is one of creating value, both social and monetary, which stays within the neighbourhood and is invested back into its communities. With the economic support through its extensive social network implemented through its Kickstarter campaign, the local and worldwide members of Homebaked have learned how to take matters into their own hands. Drawing on over four years of embedded PhD research, 24 Notebooks and personal experience as a volunteer and CLT board member, this paper aims to make visible the continuous shifts between a tentative agonistic framework between art biennial, artist and creative citizens as cultural co-producers, as they challenge and influence local economic drivers. The paper questions if artists and biennial, with their local and international communities, are capable of creating an ‘agonistic public sphere’ (Mouffe, 2007), where they can address one another in the co-production of new cultural and economic infrastructures to create social change.